A review of metal catalysts for lithium-sulfur battery applications - Shuai Li (E3S Web of Conferences)
When compared to ordinary lithium batteries now on the market, lithium-sulfur batteries stand out as the future research direction for energy storage systems owing to their higher volumetric energy density, theoretical specific energy, and gravimetric energy density. However, Li-S batteries’ drawbacks have significantly impeded their use and commercialization. A series of problems such as shuttle effects and volume expansion can remarkably reduce the service lifespan of Li-S batteries. By adding metal catalysts to the positive electrode of Li-S batteries, it is possible to improve the reaction kinetics of these batteries and efficiently address issues like the shuttle effect. During the paper, metal catalysts are separated into three groups based on the many ways they express themselves: metal single-atom catalysts, metal nanocatalysts, and metal compound catalysts. Metal single atom catalysts have catalytic active sites that are shaped like a single metal atom. Metal nanocatalysts are catalysts composed of metal particles with a size of 1-100 nm. Metal compound catalysts refer to catalysts composed of compounds formed by metals and other elements (such as oxygen, nitrogen, sulfur, etc.), including metal oxides, metal nitrides, metal sulfides, etc. It also lists and summarises the research progress of previous generations for the reference of related personnel.